Peran Notaris Dalam Memberikan Pelayanan Hukum Gratis Bagi Masyarakat Kurang Mampu - Zubairi, M Zahid Qutub (Media Hukum Indonesia (MHI), 2025)
This study examines the obligation of Notaries to provide free legal services to underprivileged communities as stipulated in Article 37 of Law Number 2 of 2014 on the Notary Office. The main issues discussed are the lack of clear standards for determining who qualifies as underprivileged and the sanctions imposed on Notaries who fail to fulfill this duty. This research employs a juridical-empirical method by analyzing legal norms, the concept of poverty under Law Number 13 of 2011, and its practical implementation. The findings reveal that although the legal framework is well established, its implementation still faces challenges, particularly in defining beneficiaries and the administrative pressures placed on Notaries. The study concludes that this obligation reflects the social function of Notaries as an officium nobile; yet, in practice, it creates a dilemma between professional ideals and legal realities. Therefore, clearer legal standards are needed to ensure effective and fair implementation.